The Morphotectonic And Neotectonic Response In Apaumagida, Enarotali And Pegunungan Legare Area Papua - Gultom, Maran; George Aiwoy, Fence; Kornelis Tipawael, Theopilus; Anakotta, Saneraro (Publisher Cv. Inara, 2023)
The verification of morpho-tectonic responses were indicated by changing of the lineament, the river segment azimuth, the mountain front sinuoucity, the mountain front facet in rock formation between lately and early geological period, controlled by neotectonic for bifurcation ratio and drainage density in Quarternary morphometry. There are three research areas namely Apaumagida Area represented by Permian–Triassic at coordinate 135°18’11,88” E - 135°43’20,14” E and 3°56’17,59” S - 4°8’28,44” S, Enarotali Area represented by Cretaceous–Paleocene at coordinate 136°18’45,08” E - 136°29’42,00” E and 3°53’34,75” S - 4°5’16,03” S, and Legare Mountain Area represented by Tertiary– Quarternary at coordinate 135° 28’ 54,87” E - 135° 47’ 16,80” E and 3° 25’ 31,17” S - 3° 6’ 6,25” S. Conclusion by different test and regression-correlation test for lineaments, river segments, mountain front sinousity and mountain face facet between Permian -Triassic, Cretaceous-Palecene and Tertiary - Quarternary are significant different to indicated that tectonic roled actively in geomorpho-tectonic in research area. Furthermore, by the neotectonic controlled, there is similarity between bifurcation ratio and drainage density in Quarternary indicated that tectonic roled actively to forms morphology in Central Mountain Papua.